Assessment of medication adherence among type 2 diabetes mellitus patients: A cross-sectional study. - Das, Santosh Kumar; Behera, Jayanti Prava; Panda, Suvendu Kumar; Panigrahy, Srikanta (Student's Journal of Health Research Africa, 2025)
Background Medication adherence is a critical component in the management of type 2 diabetes mellitus (T2DM), directly influencing glycemic control and the risk of complications. However, adherence remains suboptimal in many settings, particularly in low- and middle-income countries, such as India. Objective To assess the level of medication adherence among T2DM patients attending a tertiary care hospital in South Odisha and identify key socio-demographic and clinical factors associated with adherence. Methods A cross-sectional observational study was conducted from August to October 2023 at MKCG Medical College and Hospital, Berhampur, involving 81 adult patients with type 2 diabetes mellitus (T2DM) who had been on pharmacotherapy for at least six months. Data were collected using a structured case record form and the Morisky Medication Adherence Scale (MMAS-8). Patients scoring ≥6 on MMAS-8 were categorized as adherent, and those scoring <6 as non-adherent. Associations between adherence and various factors were analyzed using chi-square tests and odds ratios. Results Among 81 patients, 57 were male (70.4%) and 24 were female (29.6%), with a mean age of 51.07 ± 11.08 years. Overall, 29.6% were adherent while 70.4% were non-adherent. Significant associations with adherence were observed for younger age <60 years (OR 5.09; 95% CI 1.32–19.6; p=0.008), literacy (OR 3.35; 95% CI 1.19–9.42; p=0.02), working lifestyle (OR 3.67; 95% CI 1.21–11.12; p=0.02), regular exercise (OR 2.97; 95% CI 1.02–8.63; p=0.04), and simpler therapy (≤2 drugs) (OR 6.69; 95% CI 1.66–26.9; p=0.002). Gender and treatment duration showed no significant association. Conclusion Medication adherence among T2DM patients in this setting was alarmingly low. Key determinants included age, education, lifestyle, physical activity, and complexity of therapy. Recommendation Interventions focusing on health literacy, lifestyle counseling, and simplified pharmacotherapy are urgently needed to improve adherence and outcomes in diabetes care.